2003
DOI: 10.2307/1543553
|View full text |Cite
|
Sign up to set email alerts
|

Complexity in Natural Microbial Ecosystems: The Guerrero Negro Experience

Abstract: The goal of this project is to describe and understand the organismal composition, structure, and physiology of microbial ecosystems from hypersaline environments. One collection of such ecosystems occurs at North America's largest saltworks, the Exportadora de Sal, in Guerrero Negro, Baja California Sur. There, seawater flows through a series of evaporative basins with an increase in salinity until saturation is reached and halite crystallization begins. Several of these ponds are lined with thick (10 cm) mic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
58
0
1

Year Published

2005
2005
2015
2015

Publication Types

Select...
4
2
2

Relationship

1
7

Authors

Journals

citations
Cited by 65 publications
(64 citation statements)
references
References 18 publications
5
58
0
1
Order By: Relevance
“…In a molecular study of anoxic sediments below a gypsum encrusted community in Salin-de-Giraud, France, the most abundant groups were the Bacteroidetes, Firmicutes, and ␣-, ␥-, and ␦-proteobacteria (41). Finally, in a 16S rRNA survey of endoevaporitic microbial communities in the salterns of Guerrero Negro, Spear et al (66) found a predominance of bacterial phylotypes affiliated with Cyanobacteria, Bacteroidetes, ␣-, ␥-, and ␦-proteobacteria, Planctomycetes, and Firmicutes. Green sulfur bacteria and ε-proteobacteria were also detected but in low numbers.…”
Section: Vol 71 2005 Phylogeny Of An Endoevaporitic Microbial Commumentioning
confidence: 97%
See 1 more Smart Citation
“…In a molecular study of anoxic sediments below a gypsum encrusted community in Salin-de-Giraud, France, the most abundant groups were the Bacteroidetes, Firmicutes, and ␣-, ␥-, and ␦-proteobacteria (41). Finally, in a 16S rRNA survey of endoevaporitic microbial communities in the salterns of Guerrero Negro, Spear et al (66) found a predominance of bacterial phylotypes affiliated with Cyanobacteria, Bacteroidetes, ␣-, ␥-, and ␦-proteobacteria, Planctomycetes, and Firmicutes. Green sulfur bacteria and ε-proteobacteria were also detected but in low numbers.…”
Section: Vol 71 2005 Phylogeny Of An Endoevaporitic Microbial Commumentioning
confidence: 97%
“…15%, the photosynthetic communities tend to form compact and highly active microbial mats on the surface of the pond floor, whereas in ponds containing between 15 and 25% salt, the mats are less compact since the photosynthetic layers tend to be embedded within the crystalline salt crust on the pond bottom. Such endoevaporitic gypsum-or halite-associated microbial systems have been reported from a number of solar salterns around the world, including those from the coasts of the Gulf of Mexico (55,66), the Mediterranean Sea (12), the Baja Peninsula (60), and the Red Sea (53). In endoevaporitic microbial ecosystems associated with gypsum deposits, several layers of oxygenic and anoxygenic phototrophs are often visible, indicating some level of stratification in the populations.…”
mentioning
confidence: 91%
“…Previous work has shown that sulfur-cycling organisms form a major metabolic and phylogenetic component of microbial mats in Guerrero Negro and similar environments (Canfield and Des Marais, 1993;Jorgensen, 1994;Risatti et al, 1994;Krekeler et al, 1997;Teske et al, 1998;Minz et al, 1999a,b;Spear et al, 2003;Sorensen et al, 2005;Ley et al, 2006). Whole-cell FISH surveys of microbial assemblages within the mat, focusing on sulfate reducers and other known monophyletic sulfur-metabolizing guilds, allow for micron-scale mapping of the spatial distribution of these organisms (for example, Minz et al, 1999a;Wieland et al, 2003;Tonolla et al, 2005;Baumgartner et al, 2006).…”
Section: Srb Spatial Distributionmentioning
confidence: 99%
“…Previous studies of these mats have characterized the bulk microbiological community structure (Risatti et al, 1994;Spear et al, 2003;Ley et al, 2006), large-scale sulfur cycling (Canfield and Des Marais, 1993;Jorgensen, 1994) and daily variations in response to the periodic redox forcing from photosynthesis (Jorgensen, 1994;Visscher et al, 2003;Decker et al, 2005). Microcoleus-dominated mats also support active sulfate reduction by aerotolerant sulfate reducers (Teske et al, 1998) in the photosynthetically active uppermost few millimeters (Canfield and Des Marais, 1993).…”
Section: Introductionmentioning
confidence: 99%
“…Little is known concerning the potential role of fermentative bacteria and/or H 2 cycling in phototrophic microbial mat systems, such as the 6-cm-thick and extremely diverse microbial mats inhabiting the saline ponds at the Exportadora de Sal SA saltern in Guerrero Negro (GN), Baja California Sur, Mexico. Recent 16S rRNA gene surveys in GN revealed an abundance of bacteria in the upper 2 mm of the mat that, based on their phylogenetic affiliation, are thought to harbor fermentative metabolisms (6,8,13,16,20,28). Similarly, previous studies have shown that the flux of H 2 from the surface of the phototrophic mats present in GN is ϳ150-fold higher during the night than during the day (9).…”
mentioning
confidence: 95%